Factor a sum or difference of cubes

Learn how to factor a sum or difference of cubes using the special factoring patterns below.

Sum of cubes

a3 + b3 = ( a + b ) × ( a2 - ab + b2 )

Difference of cubes

a3 - b3 = ( a - b ) × ( a2 + ab + b2 )

Example #1: 

Factor the sum of cubes x3 + 27

First rewrite x3 + 27 so it will have the same format as a3 + b3

x3 + 27 = x3 + 33

Let a = x and let b = 3

a3 + b3 = ( a + b ) × ( a2 - ab + b2 )

x3 + 33 = (x + 3) × (x2 - x×3 + 32)

x3 + 33 = (x + 3) × (x2 - 3x + 9)

Check

(x + 3) × (x2 - 3x + 9) = x(x2 - 3x + 9) + 3(x2 - 3x + 9)

(x + 3) × (x2 - 3x + 9) = x3 - 3x2 + 9x + 3x2 - 9x + 27

(x + 3) × (x2 - 3x + 9) = x3 - 3x2 + 3x2 +9x - 9x + 27

Everything in red is equal to 0

(x + 3) × (x2 - 3x + 9) = x3 + 27

Example #2: 

Factor the difference of cubes x3 - 64

First rewrite x3 - 64 so it will have the same format as a3 - b3

x3 - 64 = x3 - 43

Let a = x and let b = 4

a3 - b3 = ( a - b ) × ( a2 + ab + b2 )

x3 - 43= (x - 4) × (x2 + x×4 + 42)

x3 - 43= (x - 4) × (x2 + 4x + 16)

Check

(x - 4) × (x2 + 4x + 16) = x(x2 + 4x + 16) - 4(x2 + 4x + 16)

(x - 4) × (x2 + 4x + 16) = x3 + 4x2 + 16x - 4x2 - 16x - 64

(x - 4) × (x2 + 4x + 16) = x3 + 4x2 + - 4x2 + 16x - 16x - 64

Everything in red is equal to 0

(x - 4) × (x2 + 4x + 16) = x3 - 64

Tricky examples showing how to factor a sum or difference of cubes


Example #3: 

Factor the difference of cubes 125x3 - 216

First rewrite 125x3 - 64 so it will have the same format as a3 - b3

125x3 - 216 = (5x)3 - (6)3

Let a = 5x and let b = 6

a3 - b3 = ( a - b ) × ( a2 + ab + b2 )

(5x)3 - (6)3 = (5x - 6)[(5x)2 + 5x × 6 + 62]

(5x)3 - (6)3 = (5x - 6)(25x2 + 30x + 36)

Example #4: 

Factor the sum of cubes x6 + 8x15

First rewrite x6 + 8x15 so it will have the same format as a3 + b3

x6 + 8x15 = (x2)3 + (2x5)3

Let a = xand let b = 2x5

a3 + b3 = ( a + b ) × ( a2 - ab + b2 )

(x2)3 + (2x5)= (x2 + 2x5) × [(x2)2- x2×2x5 + (2x5)2]

(x2)3 + (2x5)= (x2 + 2x5) × (x4 - 2x7 + 4x10)

(x2)3 + (2x5)= x2(1 + 2x3) × x4(1 - 2x3 + 4x6)

(x2)3 + (2x5)= x6(1 + 2x3)×(1 - 2x3 + 4x6)

Recent Articles

  1. Irrational Root Theorem - Definition and Examples

    Dec 01, 21 04:17 AM

    What is the irrational root theorem? Definition, explanation, and easy to follow examples.

    Read More

Enjoy this page? Please pay it forward. Here's how...

Would you prefer to share this page with others by linking to it?

  1. Click on the HTML link code below.
  2. Copy and paste it, adding a note of your own, into your blog, a Web page, forums, a blog comment, your Facebook account, or anywhere that someone would find this page valuable.